2016
DOI: 10.1021/acs.jmedchem.6b01204
|View full text |Cite
|
Sign up to set email alerts
|

Insights of a Lead Optimization Study and Biological Evaluation of Novel 4-Hydroxytamoxifen Analogs as Estrogen-Related Receptor γ (ERRγ) Inverse Agonists

Abstract: We evaluated the in vitro pharmacology as well as the absorption, distribution, metabolism, excretion, and toxicity (ADMET) properties of chemical entities that not only were shown to be highly selective agonists for ERRγ but also exhibited enhanced pharmacokinetic profile compared with 3 (GSK5182). 6g and 10b had comparable potency to 3 and were far more selective for ERRγ over the ERRα, -β, and ERα. The in vivo pharmacokinetic profiles of 6g and 10b were further evaluated, as they possessed superior in vitro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Recombinant human IL-6 is obtained from Prospec Protein Specialists (East Brunswick, NJ, USA, Cat#cyt-213), and GSK5182 was synthesized as previously described [ 28 , 34 , 35 , 45 ]. For immunohistochemical staining of endogenous ERRγ, rabbit anti-ERRγ serum was generated using a peptide (404-AGQHMEDPRRAGKMLM-419) from mouse ERRγ helix 9 [ 46 ] (AbFrontier/Young in Frontier, Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recombinant human IL-6 is obtained from Prospec Protein Specialists (East Brunswick, NJ, USA, Cat#cyt-213), and GSK5182 was synthesized as previously described [ 28 , 34 , 35 , 45 ]. For immunohistochemical staining of endogenous ERRγ, rabbit anti-ERRγ serum was generated using a peptide (404-AGQHMEDPRRAGKMLM-419) from mouse ERRγ helix 9 [ 46 ] (AbFrontier/Young in Frontier, Seoul, Korea).…”
Section: Methodsmentioning
confidence: 99%
“…It also involved in iron homeostasis through regulating the expression of hepatic iron regulating hormone, hepcidin [ 32 ]. Although ERRγ is constitutively active, it exhibits limited affinity toward many synthetic ligands, including 4-hydroxytamoxifen (4-OHT), which act as an inverse agonist by blocking the binding of ERRγ to response elements on the regulatory regions of target genes [ 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported that the selective ERRg inverse agonist GSK5182 enhances NIS-mediated radioiodine uptake in ATC cells with either KRAS or BRAF mutations, promoting enhanced radioiodine therapy responsiveness in vitro (9). Toward discovering novel ERRg inverse agonists, we also reported several lead optimization studies including 4-hydroxytamoxifen analogue synthesis and biological evaluation (10,11). This finding provided a rationale for exploring new ERRg inverse agonists that effectively enhance NIS function in vivo and show potential for clinical translation to patients with ATC.…”
Section: Introductionmentioning
confidence: 94%
“…Kim et al reported the short and efficient synthesis of alcohol analogues of tamoxifen via Mitsunobu reaction and biological evaluation towards estrogen-related receptor γ (ERRγ) inverse agonist (Scheme 94). [98] The synthesis involved the Mitsunobu reaction of 482 with corresponding alcohols to afford 483 in 15-99% yields followed by reduction of methyl ester group and deprotection of pivaloyl group (piv) by LiAlH 4 gave 484 in 3-99% yield as Z-isomer. Corresponding Z-485 was synthesized in 17% yield as HCl salt in the presence of 1 M aqueous HCl mixed with CH 2 Cl 2 /CH 3 OH solution.…”
Section: Nucleophilic Substitution Reactionmentioning
confidence: 99%